2000
DOI: 10.4269/ajtmh.2000.62.329
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Echinococcus granulosus infection: a case-control study.

Abstract: Abstract. Despite the importance of cystic hydatid disease worldwide, no case-control study evaluating the risk factors for Echinococcus granulosus infection has been published to date. Thus, we carried out a hospital study to quantify different risk factors associated with the disease in a province marked by a high incidence of hydatidosis (Soria, Spain). The study population was composed of 127 cases and 127 controls matched by sex, age, and residence. Odds ratios (ORs) for hydatidosis decreased inversely wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 7 publications
7
19
1
2
Order By: Relevance
“…The results are in concurrence with previous study (Khurana et al, 2007) carried out at a super specialty hospital revealing significant increase (p < 0.001) in seropositivity during the last 5 years (23.12 %, 1999 -2003) as compared with previous years (10.97 %, 1984 -1998), and a similar increase (p < 0.001) in positive Casoni's test (33.83 %, 1999 -2003 versus 21.38 %, 1984 -1998) during the same time period among suspected cases visiting this hospital. A hospital study to quantify different risk factors (Campos-Bueno et al, 2000) associated with the disease was carried out in a province marked by a high incidence of hydatidosis (Soria, Spain) and also found that odds ratios (ORs) for hydatidosis increased with the number of dogs and years of coexistence with them. The occupational distribution of patients may vary widely from country to country depending on epidemiological and socio-economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in concurrence with previous study (Khurana et al, 2007) carried out at a super specialty hospital revealing significant increase (p < 0.001) in seropositivity during the last 5 years (23.12 %, 1999 -2003) as compared with previous years (10.97 %, 1984 -1998), and a similar increase (p < 0.001) in positive Casoni's test (33.83 %, 1999 -2003 versus 21.38 %, 1984 -1998) during the same time period among suspected cases visiting this hospital. A hospital study to quantify different risk factors (Campos-Bueno et al, 2000) associated with the disease was carried out in a province marked by a high incidence of hydatidosis (Soria, Spain) and also found that odds ratios (ORs) for hydatidosis increased with the number of dogs and years of coexistence with them. The occupational distribution of patients may vary widely from country to country depending on epidemiological and socio-economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Campos-Bueno et al (20) in Spain have evaluated several risk factors in a case-control study involving 127 patients with proven CE cases and 127 The risk of infection was highest in small places with up to 500 inhabitants and increased with the number of dogs in the family and the number of years of coexistence with them. Further important risk factors were dogs having access to raw viscera of slaughter animals and dogs kept loose and able to enter dwellings.…”
Section: Epidemiologymentioning
confidence: 99%
“…Whether or not dog ownership or contact with dogs are risk factors for human CE is controversial. Some studies could not find any significant associations (Carmona et al 1998;Dowling and Torgerson 2000;Rafiei et al 2007;Harandi et al 2011), while other studies did (Campos-Bueno et al 2000;Moro et al 2008). In Kosovo, as in the neighbouring Balkan countries, the dog populations are not registered and free roaming and ownerless dogs easily have access to uncooked offal and carcasses.…”
Section: Introductionmentioning
confidence: 98%